2024
DOI: 10.1007/s00018-023-05071-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autocrine HGF maturation overcomes cetuximab resistance in colorectal cancer

Vivian Truong Jones,
Ramona Graves-Deal,
Zheng Cao
et al.

Abstract: Although amplifications and mutations in receptor tyrosine kinases (RTKs) act as bona fide oncogenes, in most cancers, RTKs maintain moderate expression and remain wild-type. Consequently, cognate ligands control many facets of tumorigenesis, including resistance to anti-RTK therapies. Herein, we show that the ligands for the RTKs MET and RON, HGF and HGFL, respectively, are synthesized as inactive precursors that are activated by cellular proteases. Our newly generated HGF/HGFL protease inhibitors could overc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Others have also documented related inhibitors of matriptase (Colombo et al, 2012(Colombo et al, , 2023Hammami et al, 2012;Marsault et al, 2014;Paszti-Gere et al, 2020;Pilgram et al, 2022;Quimbar et al, 2013;Sun et al, 2017) and hepsin (Blay et al, 2020;Knaff et al, 2022;Kwon et al, 2016Kwon et al, , 2017Kwon et al, , 2021Pant et al, 2018), along with inhibitory antibodies targeting HGFA (Ganesan et al, 2009;Wu et al, 2007), matriptase (Tamberg et al, 2019), and hepsin (Ganesan et al, 2012;Koschubs et al, 2012) but no clinical development has been observed thus far. We have demonstrate that these inhibitors exert potent anticancer activity in breast (Belitskin et al, 2023;Damalanka, Han, et al, 2019;Han et al, 2014), prostate (Han et al, 2016), lung (Damalanka et al, 2021;Owusu, Thomas, et al, 2017), colon (Jones et al, 2024), and in animal models of lung (Damalanka, Han, et al, 2019) and pancreatic cancer (Mekapogu et al, 2023).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Others have also documented related inhibitors of matriptase (Colombo et al, 2012(Colombo et al, , 2023Hammami et al, 2012;Marsault et al, 2014;Paszti-Gere et al, 2020;Pilgram et al, 2022;Quimbar et al, 2013;Sun et al, 2017) and hepsin (Blay et al, 2020;Knaff et al, 2022;Kwon et al, 2016Kwon et al, , 2017Kwon et al, , 2021Pant et al, 2018), along with inhibitory antibodies targeting HGFA (Ganesan et al, 2009;Wu et al, 2007), matriptase (Tamberg et al, 2019), and hepsin (Ganesan et al, 2012;Koschubs et al, 2012) but no clinical development has been observed thus far. We have demonstrate that these inhibitors exert potent anticancer activity in breast (Belitskin et al, 2023;Damalanka, Han, et al, 2019;Han et al, 2014), prostate (Han et al, 2016), lung (Damalanka et al, 2021;Owusu, Thomas, et al, 2017), colon (Jones et al, 2024), and in animal models of lung (Damalanka, Han, et al, 2019) and pancreatic cancer (Mekapogu et al, 2023).…”
mentioning
confidence: 89%
“…Shown is plasma concentration of compounds over time after a 20 mg/kg IP dose. The terminal half-life (t 1/2 ) was calculated to be 2.0 h for ZFH7116 (Jones et al, 2024) and 2.2 h for PK-1-89 (Sotiropoulou et al, 2022). The C max and AUC for ZFH7116 is 23,300 ng/mL and 28,500 ng h/mL and for PK-1-89 is almost double that of ZFH7116 with 45,300 ng/mL and 59,100 ng h/mL.…”
Section: Multiplex Substrate Profiling By Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Ac-L-Allyl Glycine Acid, (S)-2-Acetamidopent-4-enoic Acid (26). Compound 25 (500 mg; 3.02 mmol) was dissolved in DCM (10 mL) followed by the addition of DIEA (1.58 mL; 9.06 mmol) and Ac 2 O (0.86 mL; 9.06 mmol) at RT and then stirring for 3 h. The solvent was removed under reduced pressure, and the residue was purified by flash chromatography using EtOAc and hexanes (1:9).…”
Section: Ac-cyclo(tyr-leu-allylamide)-arg(pbf)-ketobenzothiazole or (...mentioning
confidence: 99%
“…Biphenyl ether macrocycle 11 was found to have the best overall profile with a t 1/2 of 4.5 h. We are currently pursuing further X-ray studies of these macrocycles and designing new derivatives based on the SAR generated herein. Several of these macrocyclic tripeptide serine protease inhibitors including 8b (VD4162) and 11 (VD5064) 26 are currently being tested for their anticancer properties, while 4 (VD4051) and 13 (VD5123) are being evaluated for their antiviral activity against SARS-CoV-2 as well as a broad panel of coronaviruses and influenza viruses which will be reported elsewhere.…”
Section: ■ Conclusionmentioning
confidence: 99%